Routledge encyclopedia of philosophy - Craig, Edward (London Routledge, 1998)
"Depth and breadth of coverage, clarity of presentation, impressive bibliographies, excellent use of cross references, and an extensive index combine to make this an impressive reference work. The contributors have addressed both current and past scholarship on world philosophy and religion and have produced a worthy successor to Macmillan's 1967 Encyclopedia of Philosophy. It will be read and understood by the educated public as well as scholars and will be a fine addition to academic and large public library reference collections."--"Outstanding Reference Sources : the 1999 Selection Sources Committee, RUSA, ALA.
v. 1. A posteriori-Bradwardine -- v. 2. Brahman-Derrida -- v. 3. Descartes-Gender and science -- v. 4. Genealogy-Iqbal -- v. 5. Irigaray-Lushi chunqiu -- v. 6. Luther-Nifo -- v. 7. Nihilism-Quantum mechanics -- v. 8. Questions-Sociobiology -- v. 9. Sociology of knowledge-Zoroastrianism -- v. 10. Index.
Keywords: Philosophy -- Encyclopedias; 1 <03> -- Filosofie. Psychologie--Naslagwerken. Referentiewerken